Juridical Analysis of Legal Protection of Children as Victims of Abuse in the Perspective of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection - Danu, Herman; Risdalina, Risdalina; M, Indra Kumalasari (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
This study discusses the Juridical Analysis of Legal Protection of Children as Victims of Abuse in the Perspective of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection. The type of research used is normative juridical research. The nature of research in this study is descriptive analytical. The type of data used is literature research. The results showed the form of legal protection for children as victims of abuse in the perspective of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Protection in the Form of Legal Protection of Children as Victims of Abuse in the Perspective of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection, in Article 69A It is stated that the form of protection given to children as victims of abuse, namely by: 1. Providing education about reproductive health, religious values, moral values. 2. Conducting social rehabilitation activities, for Child Victims of Abuse. 3. Conduct psychosocial assistance during treatment until recovery. 4. Provision of protection and assistance at every level of examination starting from investigation, prosecution, to examination in court hearings.